2016
DOI: 10.3390/biom6010008
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of the Glucuronyltransferases GlcAT-P and GlcAT-S of Drosophila melanogaster: Distinct Activities towards the O-linked T-antigen

Abstract: The Drosophila melanogaster glucuronyltransferases dGlcAT-S and dGlcAT-P were reported to be expressed ubiquitously and results of in vitro activity assays indicate a functional redundancy. We analyzed both transferases in vivo and in vitro and could show significant differences in their activity towards N-and O-glycoproteins in vivo. While GlcAT-P is able to use N-linked N-acetyllactosamine chains and the O-linked T-antigen as a substrate to form non-sulfated HNK1- (GlcAβ1-3Galβ1-4GlcNAcβ1-) and glucuronyl-T-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…18% of T antigen in the embryo has been found to be further modified, predominantly by glucuronic acid (GlcA) ( Aoki et al, 2008 ). Of the three GlcA transferases found in Drosophila only GlcAT-P is robustly capable of adding GlcA onto the T O-glycan structure in cells ( Breloy et al, 2016 ; Itoh et al, 2018 ; Kim et al, 2003 ). To examine if the specific defect in germband invasion that we observed by blocking the formation of T antigen is due to the need for a further elaboration by GlcA, we utilized a lethal MI{MIC} transposon insertion mutant in the GlcAT-P gene.…”
Section: Resultsmentioning
confidence: 99%
“…18% of T antigen in the embryo has been found to be further modified, predominantly by glucuronic acid (GlcA) ( Aoki et al, 2008 ). Of the three GlcA transferases found in Drosophila only GlcAT-P is robustly capable of adding GlcA onto the T O-glycan structure in cells ( Breloy et al, 2016 ; Itoh et al, 2018 ; Kim et al, 2003 ). To examine if the specific defect in germband invasion that we observed by blocking the formation of T antigen is due to the need for a further elaboration by GlcA, we utilized a lethal MI{MIC} transposon insertion mutant in the GlcAT-P gene.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that both dGlcAT-P and dGlcAT-S can catalyze glucuronylation of N -linked HNK-1 epitope (GlcAβ1-3Galβ1-4GlcNAc; Kim et al, 2003; Breloy et al, 2016). However, the expression level of HNK-1 epitope was hardly reduced in dGlcAT-P null mutant larvae (Pandey et al, 2011), indicating that dGlcAT-P was not the key enzyme for HNK-1 epitope glucuronylation in Drosophila larvae.…”
Section: Discussionmentioning
confidence: 99%
“…Three Drosophila β1,3-glucuronyltransferases (dGlcATs), dGlcAT-I (DmGlcAT-I), dGlcAT-S (DmGlcAT-BSI), and dGlcAT-P (DmGlcAT-BSII), have been reported in Drosophila . Previous studies showed that both dGlcAT-P and dGlcAT-S could transfer GlcA to T antigen in vitro , whereas only dGlcAT-P modified T antigen in S2 cells (Kim et al, 2003; Breloy et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, although one sialyltranseferase (SiaT) has been identified in Drosophila , it does not show catalytic activity for the transfer of sialic acid (Sia) to T antigen (Koles et al, 2004 ). Instead of the synthesis of sialylated T antigen in Drosophila , glucuronylated T antigen is produced by β1, 3-glucuronyltransferase-P (dGlcAT-P), which predominantly transfers glucuronic acid (GlcA) to the Gal residue in a β1, 3-linkage (Kim et al, 2003 ; Breloy et al, 2016 ; Itoh et al, 2018 ). Therefore, Drosophila glucuronylated T antigen is considered to correspond to mammalian sialylated T antigen because the two glycan structures contain negatively charged monosaccharides, namely, GlcA and Sia.…”
Section: Introductionmentioning
confidence: 99%